Engaging with the affiliative system through mindfulness: The impact of the different types of positive affect in psychosis. Issue 3 (15th November 2018) - Martins, M.J.; Marques, C.; Barreto Carvalho, C.; Macedo, A.; Pereira, A.T.; Castilho, P.
Abstract: Objectives: We aimed to explore associations between positive and negative symptoms, mindfulness, positive affect, and social safeness; and to understand the mediator role of positive emotions in the relationship between mindfulness and social safeness. Method: Fifty‐six participants with a psychotic disorder were assessed with measures of mindfulness, negative and positive symptoms, positive affect, and social safeness. Results: All variables were associated with each other except for positive symptoms and active affect. Mindfulness predicted social safeness through safe affect, when controlling for positive and negative symptoms. Conclusions: This study contributes to knowledge of mechanisms behind social safeness adding the role of mindfulness and activation of positive emotions. The continuing study of mindfulness as an important mechanism for social safeness will allow further improvement of interventions for psychosis.